A Sociotechnical Review of Carbon Capture, Utilization, and Storage (CCUS) Technologies for Industrial Decarbonization: Current Challenges, Emerging Solution, and Future Directions - Ritu Bala; Manpreet Kaur; Himani Thakur; Piyush Kashyap; Arun Karnwal; Tabarak Malik (International Journal of Chemical Engineering, 2025)
Industrial decarbonization is crucial for mitigating climate change, with carbon capture, utilization, and storage (CCUS) technologies playing a key role in reducing emissions from hard-to-abate sectors such as steelmaking, cement production, and chemical manufacturing. This review adopts a sociotechnical perspective to examine the challenges, emerging solutions, and future CCUS development and implementation prospects. Recent advancements in CCUS encompass postcombustion, precombustion, oxy-fuel combustion, and direct air capture (DAC), facilitating enhanced carbon capture efficiency. Utilization pathways diversify, converting CO2 into synthetic fuels, chemicals, and materials. Storage techniques range from geological sequestration to innovative approaches like mineralization and ocean-based storage. However, significant barriers persist. Technically, the high energy demand and scalability limitations of CCUS systems present challenges, while economic hurdles such as high costs and insufficient market incentives hinder widespread adoption. Social factors, including public perception and environmental justice concerns, further complicate deployment. Regulatory frameworks remain underdeveloped, with gaps in governance obstructing progress. Emerging solutions are targeting these barriers, with innovations in materials science improving storage efficiency and capture performance. Artificial intelligence and machine learning are enhancing system optimization and monitoring. Hybrid approaches integrating CCUS with renewable energy and collaborative public–private models show promise. Future research should focus on integrating CCUS technologies with societal needs and policy frameworks, prioritizing economic incentives, regulatory development, and addressing gaps in storage safety and lifecycle assessments. CCUS, within a circular carbon economy, presents substantial potential for sustainable industrial practices.